2011
DOI: 10.1016/j.jeconom.2010.03.030
|View full text |Cite
|
Sign up to set email alerts
|

Edgeworth expansions for realized volatility and related estimators

Abstract: This paper shows that the asymptotic normal approximation is often insufficiently accurate for volatility estimators based on high frequency data. To remedy this, we derive Edgeworth expansions for such estimators. The expansions are developed in the framework of small-noise asymptotics. The results have application to Cornish-Fisher inversion and help setting intervals more accurately than those relying on normal distribution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Goncalves and Meddahi (2004) and Zhang, Mykland, and Aït-Sahalia (2005a) have studied Edgeworth expansions of these types of results, while the former also derived a bootstrapped version to improve the finite sample performance of the feasible version of the theory.…”
Section: Commentsmentioning
confidence: 99%
“…Goncalves and Meddahi (2004) and Zhang, Mykland, and Aït-Sahalia (2005a) have studied Edgeworth expansions of these types of results, while the former also derived a bootstrapped version to improve the finite sample performance of the feasible version of the theory.…”
Section: Commentsmentioning
confidence: 99%
“…By Withers and Nadarajah (2012), the expansions (1.5)-(1.7), (1.9)-(1.11) remain true for 21) and p X (x) = p(x) is the density of X, if…”
Section: Introductionmentioning
confidence: 97%
“…The Cornish Fisher expansions also have applications in many applied areas, including risk measures for hedge funds, margin setting of index futures, structural equation models, modified sudden death tests, blind inversion of Wiener systems, GPS positioning accuracy estimation, steady-state simulation analysis, blind separation of post-nonlinear mixtures, cycle time quantile estimation, estimation of the maximum average time to flower, performance of Skart, testing and evaluation, load flow in systems with wind generation, Value-at-Risk portfolio optimization, quantile mechanics, channel capacity in communications theory, economics, financial intermediation and physics. Three of the most recent papers applying Cornish Fisher expansions to these areas are: Alfredo and Arunachalam (2011), Simonato (2011) and Zhang et al (2011).…”
Section: Introductionmentioning
confidence: 99%
“…The bootstrap could also be useful for inference in the context of these estimators. Indeed, Zhang et al (2011) showed that the asymptotic normal approximation is often inaccurate for the subsampling realized volatility estimator, whose finite sample distribution is skewed and heavy tailed. They proposed Edgeworth corrections for this estimator as a way to improve upon the standard normal approximation.…”
Section: Introductionmentioning
confidence: 99%